Клінічний випадок одонтогенної розлитої флегмони обличчя - Варжапетян, А. С.; Кокарь, Оксана Олександрівна; Varzhapetian, A. S.; Kokar, O. O. (Запорізький державний медико-фармацевтичний університет, 2025)
Мета роботи – опис та обговорення незвичайного клінічного випадку розлитої флегмони обличчя, щоб підвищити обізнаність і компетентність клініцистів, яким такі випадки можуть трапитися на практиці. Матеріали і методи. Під час дослідження здійснено клінічний аналіз епізодів стаціонарного лікування пацієнтів з одонтогенною флегмоною одного або кількох клітковинних просторів щелепно-лицевої ділянки. Усі клінічні випадки детально проаналізовано, складено план лікування. У цій статті наведено опис випадку, на наш погляд, найскладнішого за аналізований період, коли госпітальний етап лікування тривав 25 діб. Результати. Пацієнтка М. віком 56 років ургентно госпіталізована у відділення щелепно-лицевої хірургії та отоларингології Комунального некомерційного підприємства «Міська лікарня екстреної та швидкої медичної допомоги» Запорізької міської ради. Хворій встановлено діагноз одонтогенної розлитої флегмони правої половини обличчя, загострення хронічного періодонтиту 4.6. Надано допомогу відповідно до стандартного внутрішнього маршруту, протоколу обстеження та лікування одонтогенних флегмон обличчя. The aim of the work is to describe and discuss an unusual clinical case of diffuse facial phlegmon in order to increase the awareness and competence of clinicians who may encounter similar cases. Materials and methods. For the study, a clinical analysis of episodes of inpatient treatment of patients with odontogenic phlegmon (cellulitis) of one or more cellular spaces of the maxillofacial region was conducted. All clinical cases underwent a thorough clinical analysis, and a treatment plan was drawn up. In this article, we present a description of a case, in our opinion, the most difficult during the studied period, with a hospital treatment period of 25 days. Results. Patient M., 56 years old, was hospitalized in the department of maxillofacial surgery and otolaryngology of the Municipal Non-Commercial Enterprise “City Hospital of Emergency and Urgent Medical Care” of the Zaporizhzhia City Council. The diagnosis was “Odontogenic diffuse phlegmon of the right half of the face. Exacerbation of chronic periodontitis 4.6”. The course of the disease was slow. The severity of the disease was due to the prevalence of the purulent process and the presence of concomitant chronic pathologies in the patient, such as diabetes mellitus, nephropathy of mixed genesis. In the hospital, the patient suffered hospital pneumonia. Several surgical interventions were performed to drain purulent foci, necrectomy, and sanitation of the oral cavity. The patient’s treatment was carried out comprehensively with the involvement of related specialists. At the time of recovery, after 25 days of inpatient treatment, the patient had significant local negative consequences of the disease and surgical intervention: facial nerve paresis, cicatricial facial deformities, muscle contracture, atrophy of the fatty tissue of half of the face.
A clinical case of diffuse odontogenic facial phlegmon
Keywords: клінічне дослідження; запальне захворювання; комплексне лікування; запалення; аналіз; clinical study; inflammatory disease; complex treatment; inflammation; analysis